How big a challenge to initiate three basic infection control practices in hospitals of Bangladesh? - Hasan, Zahidul (Bangladesh Journal of Medical Microbiology, 2012)
Not available DOI: http://dx.doi.org/10.3329/bjmm.v4i2.10763